Doppler backscattering systems on the Globus-M2 tokamak. (1st January 2022) - Yashin, A.Y.; Bulanin, V.V.; Gusev, V.K.; Minaev, V.B.; Petrov, A.V.; Petrov, Y.V.; Ponomarenko, A.M.; Varfolomeev, V.I.
Abstract: Doppler backscattering (DBS) was successfully previously used on the Globus-M tokamak. The diagnostic was utilised in the form of either a single-frequency or a four-frequency dual homodyne system. It was used primarily for the study of zonal flows, filaments and Alfvén eigenmodes. These phenomena are worth being studied both on the periphery and in the core region of the plasma in a tokamak. For this specific reason two multifrequency DBS systems were installed on the upgraded Globus-M2 tokamak. The first four-frequency system with dual homodyne detection had already been used on the Globus-M tokamak and has lower probing frequencies which provide measurements from the periphery plasma. The second and new six-frequency DBS system was installed with a non-linear transmission line that was adapted to generate probing signals at frequencies 50, 55, 60, 65, 70 and 75 GHz. In general, the range of probing frequencies corresponds to the region of critical plasma densities from 5 × 10 18 to 7 × 10 19  m −3 at normal incidence. The pyramidal horn antennas are located inside the vacuum vessel with a special cardan-like rotator outside the camera so as to tilt antennas in the toroidal and poloidal directions. A previously developed code was applied to simulate 3D raytracing for all frequency channels. Calculations were carried out for different angles of incidence and for different electron density distributions in order to investigate the possibilities of the implementation of radial and poloidal correlation Doppler reflectometry. Examples of the DBS system application for study of plasma properties in the Globus-M2 tokamak are presented.